Diet of the lizard Ecpleopus gaudichaudii (Gymnophthalmidae) in Atlantic Rainforest, state of Rio de Janeiro, Brazil - Maia,Thiago (2011)
In this study we analyzed the diet of the gymnophthalmid lizard Ecpleopus gaudichaudii Duméril & Bibron, 1839, a typical inhabitant of the forest-floor leaf litter, in an Atlantic Forest area in the state of Rio de Janeiro, southeastern Brazil. The 26 individuals sampled during the study had a mean snout-vent length (SVL) of 36.2 ± 4.2 mm and a mean jaw width (JW) of 4.1 ± 0.5 mm. We did not find differences in SVL between males and females, though the sexes differed in JW when the effect of body size was factored out, with females presenting higher values. The diet of the lizards was composed exclusively of arthropods, especially isopods and orthopterans. The similarity in trophic niches among seasons (volumetric and numerical proportions of prey categories consumed) were 0.096 and to 0.43, respectively. There were also no detectable seasonal differences in mean number and mean volume of prey ingested, as well as no significant influence of lizard SVL on prey number and of lizard JW on mean prey volume, which may reflect the tendency of E. gaudichaudii to feed on few, relatively large prey.